The role of mesenchymal stem cells in the treatment of ARDS and cytokine storms in COVID-19 - Waseem, Muhammad; Altaf, Hamza; Hussain, Nageen; Mushtaq, Sobia; Siddique, Samavia (Journal of Clinical Trials and Experimental Investigations, 2025)
The COVID-19 pandemic continues to challenge global healthcare systems, particularly due to the lack of effective treatment options for patients who develop acute respiratory distress syndrome (ARDS), cytokine storms, and long-term pulmonary complications. While antiviral agents and vaccines have mitigated some of the burden, these approaches are not universally effective—especially against emerging variants. In this context, mesenchymal stem cells (MSCs) have emerged as a promising therapeutic strategy due to their unique immunomodulatory and regenerative properties.